2004
DOI: 10.1111/j.1467-8551.2004.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap between Rhetoric and Reality: Line Managers and the Protection of Job Security for Ill Workers in the Modern Workplace

Abstract: In the light of the long-standing concern in management regarding the gap that can arise between organizational policy prescriptions and line-management practice, the purpose of this article is to provide insights into the nature and causes of that gap. The particular focus of analysis is the line manager's role in facilitating the employment security of employees who have contracted serious illness, injuries or disabilities. More specifically, the article presents findings from four case-study organizations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
0
10

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(116 citation statements)
references
References 26 publications
4
102
0
10
Order By: Relevance
“…To theorize these experiences we use the work of Harding (2013) which furthers understanding of Elizabeth's aspirations post diagnosis, and the challenges she confronts in the construction of an inclusive work context. In constructing inclusive work contexts for disabled people, consideration of adjustments is required along with the involvement of line managers (Cunningham et al, 2004;Dibben et al, 2001) and colleagues (Swain and French, 2008). However, it can fall to disabled workers themselves to make such arrangements (Foster, 2007).…”
Section: Conceptualizing Dementia In the Workplacementioning
confidence: 99%
“…To theorize these experiences we use the work of Harding (2013) which furthers understanding of Elizabeth's aspirations post diagnosis, and the challenges she confronts in the construction of an inclusive work context. In constructing inclusive work contexts for disabled people, consideration of adjustments is required along with the involvement of line managers (Cunningham et al, 2004;Dibben et al, 2001) and colleagues (Swain and French, 2008). However, it can fall to disabled workers themselves to make such arrangements (Foster, 2007).…”
Section: Conceptualizing Dementia In the Workplacementioning
confidence: 99%
“…107 Several scholars ascribe to poor implementation the divide between espoused people-management policies and the reality experienced by employees subject to the policies. [107][108][109][110] This section critically reviews the literature on implementation fidelity and considers the concept in relation to the implementation of policies in HRM. It begins by examining existing descriptions of a model of implementation fidelity.…”
Section: Policy-practice Link and Implementation Fidelitymentioning
confidence: 99%
“…Policy-makers themselves would no doubt value understanding the organisational processes through which policies are implemented and the factors (organisational, group and individual) that may facilitate and impede implementation fidelity. For example, Cunningham et al 107 in an analysis of four case studies, identified a range of factors that militated against the implementation of a policy on job security for ill workers. These included contradictory policy requirements, weakness in training, and various work and budgetary pressures.…”
Section: Fidelity Of Hr Policymentioning
confidence: 99%
“…The devolution of HR decision-making to line management inevitably means there is greater scope for disparity and inconsistencies between the policy formulated at senior HR level and the actual decisions taken by line managers. Legge (1995) argues that HR policy (rhetoric) can be somewhat divorced from actual practice (reality) and other research tends to support this view (Cunningham, James, & Dibben, 2004;Purcell, Kinnie, Hutchinson, Rayton, & Swart, 2003;Whittaker & Marchington, 2003). As HR policies cascade down the organizational hierarchy, middle and line managers become relevant stakeholders in influencing how HR policies are interpreted and enacted.…”
Section: Hr and Wlb Policy And Practice -The Role Of Line Managersmentioning
confidence: 99%